Penentuan Massa Iddah Bagi Istri yang di Talak di Luar Sidang Pengadilan Agama - M. Sirojudin Siddiq, M.H (Al Qadhi Journal of Islamic Family Law, 2019)
Abstract In the fiqh the determination of the beginning of the period 'iddah depends on the condition of the woman when divorce occurs in a sacred state while menstruating, has been collected during the holy period or not menstruating. menstrual women divorced during menstruation or who have gathered at the time of divorce 'the iddah began to be counted in the aftermath of the holy period. And for women who are not menstruating,' the date is calculated from the day of the fall. In KHI ‘iddah is calculated since the divorce determination has a permanent legal force. Determination of permanent legal force if there is no legal remedy from the defendant during the deadline for filing legal proceedings. If there is a legal remedy, then ‘iddah is calculated since the legal determination has been fixed. The implementation of the determination of the beginning of the period ah iddah is carried out by KUA based on the date of the top / main sentence contained in the contents of the actacerai. The top date on the divorce certificate is the date on which the actatak readings on the divorce divorce or the date of the decision of the legal force remain in the claim.